Freeze-drying-free and low-cost method for rapidly preparing large-size elastic nanofiber aerogel

Through freeze-drying ice dissolution induced coordination crosslinking reaction and atmospheric pressure drying, the existing fiber aerogel preparation process is solved, and the rapid and low-cost large-scale preparation of large-size elastic nanofiber aerogels is achieved. It has good mechanical properties and structural controllability, and is suitable for a variety of application fields.

CN119505348APending Publication Date: 2025-02-25TIANJIN POLYTECHNIC UNIV

Patent Information

Application Number
CN202411393864.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing fiber aerogel preparation process is long, the energy consumption is high, the preparation cost is high, the efficiency is low, the difficulty in preparing large sizes, the poor dimensional stability is difficult and the mechanical properties are difficult to take into account.

Method used

Three-dimensional nanofiber aerogels were prepared on a large scale using freeze-dried ice dissolution induced coordination crosslinking reaction, and atmospheric drying. The specific steps include dispersing the nanofibers and polysaccharide polymers in water to form a dispersion liquid, forming a solidification block after solidification treatment, and then performing a coordination crosslinking reaction in the ethanol solution of the metal cationic salt, and finally removing the solvent under normal pressure.

Benefits of technology

It has achieved rapid, low-cost, large-scale preparation of large-size elastic nanofiber aerogels, with good mechanical properties and structural controllability, and is suitable for sound absorption and noise reduction, heat insulation, filtration and separation, and tissue engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505348A_ABST
    Figure CN119505348A_ABST
Patent Text Reader

Abstract

The invention discloses a method for quickly preparing large-size elastic nanofiber aerogel without freeze-drying and with low cost. The method comprises the following steps: dispersing nanofibers and polysaccharide macromolecules in water to form a dispersion liquid; carrying out solidification treatment on the dispersion liquid to form a solidified block; putting the solidified block into an ethanol solution of metal cation salt, and carrying out coordination reaction to form wet gel; and removing the solvent in the aerogel under a normal pressure condition to obtain the nanofiber aerogel. The three-dimensional nanofiber aerogel is rapidly prepared on a large scale through freeze-drying-free ice dissolution induced coordination reaction and normal-pressure drying for the first time, the three-dimensional nanofiber aerogel is composed of fibers and a macromolecular coordination cross-linked network, the fibers are firmly bonded through the macromolecular coordination network, and the three-dimensional nanofiber aerogel has an interconnected pore structure and a wide adjustable range of the pore structure and can be used for preparing the three-dimensional nanofiber aerogel. The fiber aerogel shows good mechanical properties, sound absorption, noise reduction, heat insulation and warmth retention properties, oil absorption and wave absorption properties, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a freeze-drying-free, low-cost and fast method for preparing large-size elastic nanofiber aerogel, belonging to the technical field of nanofibers. Background Art

[0002] Three-dimensional nanofiber aerogel has the advantages of light weight, high porosity, large specific surface area, and good pore connectivity, and shows broad application prospects in the fields of sound absorption and noise reduction, thermal insulation, filtration separation, and tissue engineering.

[0003] The drying methods currently used to prepare aerogels mainly include supercritical drying and freeze drying.

[0004] The supercritical drying method is a drying technology that controls and adjusts the pressure and temperature so that the solvent reaches its own critical point during the drying process, thereby completing the supercritical transition from liquid phase to gas phase. In the supercritical state, the surface tension of the solvent drops to zero. The solvent in this state has no obvious surface tension, and can complete the transformation of wet gel to aerogel while maintaining the skeleton structure. This drying method can effectively avoid the generation of gas / liquid interface, so there is no meniscus tension. The gel can retain a relatively complete three-dimensional network structure during the drying process, and can also avoid the residual solvent substances in the pores. For example, the Chinese patent with application number CN201910892859.0 discloses the use of supercritical drying method to prepare ultra-low density aerogel and related products. Although the prepared aerogel has good formability, the supercritical drying method requires special supercritical drying equipment, the equipment process is complex, the operation is cumbersome, there are safety hazards, and the temperature and pressure requirements are very high, the cost is high, the energy consumption is large, and it is difficult to achieve industrial mass production.

[0005] Compared with the supercritical drying method, the freeze-drying method for preparing aerogels is to first disperse the nanofibers into a solvent and form a nanofiber dispersion through high-speed shearing, then freeze the dispersion into a solidified block, and further sublimate the solvent under a vacuum environment to form a three-dimensional nanofiber aerogel. The advantage of this method over supercritical drying is that it can better maintain the original properties and structure of the material, while the operation is relatively simple and has a wider range of applications. Si et al. [Si, Y., Yu, J., Tang, X., Ge, J. & Ding, B. Ultralight nanofiber-assembled cellular aerogels with superelasticity and multifunctionality. Nat. Commun. 5, 5802 (2014).] homogeneously dispersed polyacrylonitrile nanofibers and silicon oxide nanofibers in a water solvent, obtained a three-dimensional nano aerogel by freezing and freeze drying, and then obtained an elastic nanofiber aerogel through a subsequent crosslinking process. However, the preparation time of the freeze-drying method is too long (48 hours), resulting in a long material preparation process. In addition, the requirements of low temperature and high vacuum environment lead to high equipment costs, long drying process, high production costs and low efficiency, making it difficult to achieve large-scale preparation.

[0006] Therefore, it is of great significance to develop a simple and low-cost method for preparing nanofiber aerogels. Summary of the invention

[0007] The technical problems to be solved by the present invention are: the existing fiber aerogel preparation process is long, the energy consumption is high, the preparation cost is high, the efficiency is low, it is difficult to prepare in large size, the dimensional stability is poor, and it is difficult to take into account the mechanical properties.

[0008] In order to solve the above technical problems, the present invention provides a method for rapidly preparing large-sized elastic nanofiber aerogels without freeze-drying and at low cost, comprising the following steps:

[0009] The first step: dispersing the nanofibers and polysaccharide polymers in water to form a dispersion;

[0010] Step 2: solidifying the dispersion to form a solidified mass;

[0011] Step 3: placing the solidified block into an ethanol solution of a metal cation salt to undergo a coordination cross-linking reaction to form a wet gel;

[0012] Step 4: Remove the solvent from the wet gel under normal pressure to obtain nanofiber aerogel.

[0013] Preferably, the raw material of the nanofiber in the first step is selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polysulfone, polystyrene, polyimide, polymethyl methacrylate, polyetherimide, polyurethane, polyamide, polyaniline, bacterial cellulose, cellulose acetate, silicon dioxide, titanium dioxide, aluminum oxide, carbon nanotubes and graphene;

[0014] The polysaccharide polymer is selected from at least one of chitosan, sodium alginate, hyaluronic acid, chitin, sodium carboxymethyl cellulose, starch, keratan sulfate and chitin.

[0015] Preferably, the solidification treatment in the second step comprises: freezing forming in a mold.

[0016] More preferably, the freezing temperature is -196 to -10°C, and the freezing time is 1 min to 1 h.

[0017] Preferably, the metal cation salt in the third step is at least one of cupric chloride, lanthanum chloride, cerous chloride, ferric chloride, cobalt chloride, nickel chloride, cupric chloride, zinc chloride, calcium chloride, zinc nitrate, ferric nitrate and cupric nitrate.

[0018] Preferably, the reaction temperature of the third step is below 0°C and the reaction time is 1 to 5 hours.

[0019] Preferably, conductive components and magnetic nanoparticles are added to the dispersion in the first step, so as to finally obtain nanofiber aerogel with magnetic conductive function, which can be used as a wave absorbing material.

[0020] In some embodiments of the present invention, the conductive component comprises pyrrole; and the magnetic nanoparticles comprise magnetic ferrosoferric oxide nanoparticles.

[0021] Preferably, the total solid content of the dispersion in the first step is 0.2-2 wt%.

[0022] In the present invention, the nanofibers in the first step are prepared by existing techniques or commercially available nanofibers; for example, they can be prepared by existing sol-gel electrospinning methods or electrospinning technology.

[0023] In some embodiments of the present invention, the process of preparing nanofibers by sol-gel electrospinning includes: first, preparing a sol of nanomaterial (at least one of silicon dioxide, titanium dioxide, aluminum oxide, carbon nanotubes and graphene) and a spinning polymer solution (the polymer may be PVA). Subsequently, the sol and the spinning polymer solution are mixed to obtain a precursor solution. The precursor solution is electrospun to obtain a hybrid nanofiber membrane, then vacuum dried to remove moisture, and finally heat treated to remove organic components to obtain a nanofiber membrane.

[0024] The present invention also provides the nanofiber aerogel prepared by the above method.

[0025] Preferably, the macroscopic shape of the nanofiber aerogel is a cylinder, a pyramid, a cube, a regular hexahedron or a regular octahedron;

[0026] And / or, the microstructure of the nanofiber aerogel is a layered porous structure, a spherical porous structure, a cylindrical porous structure or an amorphous porous structure.

[0027] Preferably, the thickness of the nanofiber aerogel is 0.1-100 mm, and the volume density is 1-20 mg / cm 3 .

[0028] Preferably, the average sound absorption coefficient of the nanofiber aerogel is 0.4 to 0.7;

[0029] And / or, the oil absorption of the nanofiber aerogel is 30 to 80 g / g.

[0030] Preferably, the effective peak width of electromagnetic wave absorption of the nanofiber aerogel is >5 GHz, and the minimum reflection loss is <-20 dB.

[0031] The present invention also provides the use of the nanofiber aerogel prepared by the above method in wave absorbing materials, sound absorption and noise reduction, heat insulation and warmth preservation, filtration separation and tissue engineering.

[0032] The present invention provides a freeze-drying-free, low-cost and rapid method for preparing large-sized elastic nanofiber aerogels. The method is a new method for preparing large-sized nanofiber aerogels at normal pressure based on coordination crosslinking reaction. The fiber aerogel is prepared under normal pressure without vacuum or supercritical drying. The entire preparation process can be completed within a few hours. The aerogel is composed of fibers and macromolecular coordination crosslinking networks. The fibers are firmly bonded by the macromolecular coordination network and have good mechanical properties.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention is the first to prepare three-dimensional nanofiber aerogels on a large scale by inducing coordination cross-linking reaction through ice dissolution without freeze-drying and drying at normal pressure.

[0035] (2) The macroscopic fiber network in the aerogel prepared by the present invention is firmly bonded together by the microscopic macromolecules formed by the coordination reaction, and thus has good mechanical properties without the need for additional cross-linking.

[0036] (3) The preparation method provided by the present invention has a simple process and strong universality, and can be applied to the preparation of a wide range of polymer-based, ceramic-based and carbon-based fiber aerogels; in addition, the preparation method has good fiber structure controllability, and can achieve precise control of the fiber aerogel structure, thickness and density by controlling the fiber content, density and freezing method.

[0037] (4) Compared with the prior art, the fiber aerogel prepared by the present invention can directly prepare a fiber aerogel with large size and good mechanical properties through a simple coordination cross-linking reaction at normal pressure, which greatly reduces the production cost and can be prepared on a large scale through a simple method. It shows great application advantages in the fields of sound absorption and noise reduction, heat insulation, tissue engineering, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Schematic diagram of the nanofiber aerogel of the present invention.

[0039] Figure 2 is an exemplary scanning electron microscope photograph of the nanofiber aerogel of the present invention. DETAILED DESCRIPTION

[0040] In order to make the present invention more clearly understood, preferred embodiments are described in detail below with reference to the accompanying drawings.

[0041] In the following examples, the materials and reagents used are all conventional commercial products unless otherwise specified; the bacterial cellulose dispersion was purchased from Guilin Qihong Technology Co., Ltd.; the silicon oxide nanofiber membrane was independently prepared by sol-gel electrospinning technology; the specific preparation process includes: first, H3PO4 was quickly added dropwise to a mixed solution of H2O and TEOS (the molar ratio of H3PO4, H2O and TEOS was 0.01:1:10), and stirred for 8 hours to obtain silica sol. At the same time, PVA powder was stirred for 5 hours in deionized water at 80°C to dissolve, forming a PVA solution with a concentration of 10wt%. Subsequently, the same mass of silica sol and PVA solution were mixed and stirred for another 8 hours to obtain a stable precursor solution. The precursor solution was electrospun to prepare PVA / SiO2 hybrid nanofiber membrane, which was then dried in a vacuum oven at 70°C for 2 h to remove moisture, and then placed in a programmed temperature muffle furnace to remove organic components to obtain a SiO2 nanofiber membrane (heating rate of 5°C / min, termination temperature of 800°C).

[0042] Example 1

[0043] A method for rapidly preparing large-sized elastic nanofiber aerogel without freeze-drying and at low cost, specifically comprising the following steps:

[0044] Step 1: Cut the silica nanofiber membrane into pieces of 5 mm × 5 mm in size, then disperse it in water and homogenize it in a high-pressure homogenizer for 1 min to form a silica nanofiber dispersion, then add sodium carboxymethyl cellulose to the dispersion and stir for 30 min to obtain a silica nanofiber / sodium carboxymethyl cellulose dispersion, the total solid content of the dispersion is 1 wt%.

[0045] Step 2: The dispersion obtained above was transferred to a mold and frozen with liquid nitrogen for 6 minutes to obtain a layered porous structure of silica nanofibers / sodium carboxymethyl cellulose frozen block.

[0046] Step 3: Transfer the above-mentioned silica nanofiber / sodium carboxymethyl cellulose frozen block to a copper nitrate / ethanol solution and react at -5°C for 3 hours to obtain a silica nanofiber-based aerogel containing ethanol and water.

[0047] Step 4: Dry the silica nanofiber-based aerogel containing ethanol and water prepared above at room temperature and pressure or heat it in a normal pressure oven at a temperature below 100°C to remove the ethanol and water, and obtain a volume density of 10 mg / cm 3 The present invention relates to a layered porous structured silicon oxide nanofiber-based aerogel. After being compressed 100 times, the plastic deformation of the aerogel is 7%, and the average sound absorption coefficient of the material is 0.56.

[0048] Example 2

[0049] A method for rapidly preparing large-sized elastic nanofiber aerogel without freeze-drying and at low cost, specifically comprising the following steps:

[0050] Step 1: Disperse the bacterial cellulose dispersion in water and homogenize in a high-pressure homogenizer for 2 minutes, then add sodium carboxymethyl cellulose to the dispersion and stir for 30 minutes to obtain a bacterial cellulose / sodium carboxymethyl cellulose dispersion, the total solid content of the dispersion is 0.6 wt%.

[0051] Step 2: The dispersion obtained above was transferred into a mold and rapidly frozen with liquid nitrogen for 3 minutes to obtain a bacterial cellulose / sodium carboxymethyl cellulose frozen block with an amorphous porous structure.

[0052] Step 3: Transfer the bacterial cellulose / sodium carboxymethyl cellulose frozen block to the copper nitrate / ethanol solution and react at -20°C for 3 hours to obtain a bacterial cellulose aerogel containing ethanol and water.

[0053] Step 4: Heat the bacterial cellulose-based aerogel containing ethanol and water prepared above in an oven at room temperature or pressure to remove ethanol and water, and obtain a volume density of 6 mg / cm 3The amorphous porous bacterial cellulose-based aerogel has a plastic deformation of only 6% after 100 compressions, an average sound absorption coefficient of the material of 0.57, and an edible oil adsorption capacity of 35g / g.

[0054] Example 3

[0055] A method for rapidly preparing large-sized elastic nanofiber aerogel without freeze-drying and at low cost, specifically comprising the following steps:

[0056] The first step: cut the silica nanofiber membrane into pieces of 5mm×5mm in size, then disperse it and a certain amount of graphene oxide in water, homogenize under high pressure for 2 minutes to obtain a silica nanofiber / graphene composite dispersion, then add sodium carboxymethyl cellulose to the dispersion and stir for 30 minutes to obtain a bacterial cellulose / sodium carboxymethyl cellulose dispersion, the total solid content of which is 0.8wt%.

[0057] Step 2: Transfer the dispersion obtained above into a mold and freeze it with liquid nitrogen for 5 minutes to obtain a frozen block of nanofibers / graphene / sodium carboxymethyl cellulose with a layered porous structure.

[0058] Step 3: Transfer the nanofiber / graphene / sodium carboxymethyl cellulose frozen block to a copper nitrate / ethanol solution and react at -20°C for 3.5h to obtain a nanofiber / graphene aerogel containing ethanol and water.

[0059] Step 4: Heat the prepared nanofiber / graphene aerogel containing ethanol and water in an oven at room temperature or pressure to remove ethanol and water, and obtain a volume density of 8 mg / cm 3 The layered porous structure nanofiber / graphene aerogel has a plastic deformation of only 6% after 100 compressions, an average sound absorption coefficient of the material of 0.58, and an edible oil adsorption capacity of 38g / g.

[0060] Example 4

[0061] A method for rapidly preparing large-sized elastic nanofiber aerogel without freeze-drying and at low cost, specifically comprising the following steps:

[0062] Step 1: Cut the silica nanofiber membrane into pieces of 5 mm × 5 mm in size, then disperse it in water and homogenize it in a high-pressure homogenizer for 1 min to form a silica nanofiber dispersion, then add sodium carboxymethyl cellulose to the dispersion and stir for 30 min to obtain a silica nanofiber / sodium carboxymethyl cellulose dispersion, the total solid content of the dispersion is 0.7 wt%.

[0063] Step 2: The dispersion obtained above was transferred into a mold and rapidly frozen with liquid nitrogen for 3 minutes to obtain a frozen block of silica nanofibers / sodium carboxymethyl cellulose having an amorphous porous structure.

[0064] Step 3: Transfer the silica nanofiber / sodium carboxymethyl cellulose frozen block to the copper nitrate / ethanol solution and react at -5°C for 3.5h to obtain a silica nanofiber-based aerogel containing ethanol and water.

[0065] Step 4: Heat the silica nanofiber-based aerogel containing ethanol and water prepared above in an oven at room temperature or pressure to remove ethanol and water, and obtain a volume density of 7 mg / cm 3 The amorphous porous structure of silica nanofiber-based aerogel has a plastic deformation of only 7% after 100 compressions, and an average sound absorption coefficient of the material is 0.55.

[0066] Example 5

[0067] A method for rapidly preparing large-sized elastic nanofiber aerogel without freeze-drying and at low cost, specifically comprising the following steps:

[0068] Step 1: Cut the silica nanofiber membrane into pieces of 1 cm×1 cm in size, then disperse it in water and homogenize it in a high-pressure homogenizer for 0.4 min to form a silica nanofiber dispersion, then add sodium alginate to the dispersion and stir for 40 min to obtain a silica nanofiber / sodium alginate dispersion, the total solid content of the dispersion is 0.4 wt%.

[0069] Step 2: The dispersion obtained above was transferred into a mold and frozen in a refrigerator for 30 minutes to obtain a silica nanofiber / sodium alginate frozen block with a layered porous structure.

[0070] Step 3: Transfer the silica nanofiber / sodium alginate frozen block to a calcium chloride / ethanol solution and react at -10°C for 3 hours to obtain a silica nanofiber-based aerogel containing ethanol and water.

[0071] Step 4: Dry the silica nanofiber-based aerogel containing ethanol and water in a room temperature environment or heat it in a normal pressure oven to remove the ethanol and water to obtain a volume density of 4 mg / cm 3 The present invention discloses a layered porous structured silicon oxide nanofiber-based aerogel. After being compressed 100 times, the plastic deformation of the aerogel is only 8%, and the average sound absorption coefficient of the material is 0.54.

[0072] Example 6

[0073] A method for rapidly preparing large-sized elastic nanofiber aerogel without freeze-drying and at low cost, specifically comprising the following steps:

[0074] Step 1: Disperse the bacterial cellulose dispersion in water and homogenize in a high-pressure homogenizer for 2 minutes, then add chitosan into the dispersion and stir for 30 minutes to obtain a bacterial cellulose / chitosan dispersion, the total solid content of the dispersion is 0.5 wt%.

[0075] Step 2: The dispersion obtained above was transferred into a mold and rapidly frozen with liquid nitrogen for 5 minutes to obtain a bacterial cellulose / chitosan frozen block with an amorphous porous structure.

[0076] Step 3: Transfer the frozen block of bacterial cellulose / chitosan to an aluminum chloride / ethanol solution and react at -15°C for 3 hours to obtain a bacterial cellulose aerogel containing ethanol and water.

[0077] Step 4: Heat the bacterial cellulose-based aerogel containing ethanol and water prepared above in an oven at room temperature or pressure to remove ethanol and water, and obtain a volume density of 5 mg / cm 3 The amorphous porous bacterial cellulose-based aerogel has a plastic deformation of only 6.8% after 100 compressions, an average sound absorption coefficient of the material of 0.56, and an edible oil adsorption capacity of 38 g / g.

[0078] Example 7

[0079] A method for rapidly preparing large-sized elastic nanofiber aerogel without freeze-drying and at low cost, specifically comprising the following steps:

[0080] Step 1: Disperse the bacterial cellulose dispersion in water and homogenize it in a high-pressure homogenizer for 2 minutes, then add chitosan to the dispersion and stir for 30 minutes to obtain a bacterial cellulose / chitosan dispersion, then add pyrrole and magnetic ferrosoferric oxide particles to the dispersion, and polymerize at 3°C ​​for 30 minutes. The total solid content of the dispersion is 1.2wt%.

[0081] Step 2: The dispersion obtained above was transferred into a mold and directionally frozen with liquid nitrogen for 5 minutes to obtain a layered structured polypyrrole / ferroferric oxide / bacterial cellulose frozen block.

[0082] Step 3: Transfer the polypyrrole / ferroferric oxide / bacterial cellulose frozen block to an aluminum chloride / ethanol solution and react at -15°C for 3 hours to obtain a bacterial cellulose-based magnetic conductive aerogel containing ethanol and water.

[0083] Step 4: Heat the bacterial cellulose-based magnetic conductive aerogel containing ethanol and water prepared above in an oven at room temperature or pressure to remove ethanol and water, and obtain a volume density of 12 mg / cm 3The amorphous porous bacterial cellulose-based magnetic conductive aerogel has an effective peak width of 7 GHz for electromagnetic wave absorption and a minimum reflection loss of -25 dB.

[0084] The exemplary physical photos of the nanofiber aerogel prepared as described above are as follows: Figure 1 As shown, the macroscopic fiber networks of the aerogel are tightly connected by a coordination macromolecular network. Figure 2 is an exemplary scanning electron microscope photograph of the nanofiber aerogel of the present invention.

[0085] The shape of the nanofiber aerogel is a cylinder, a pyramid, a cube, a regular hexahedron or a regular octahedron; the microstructure is a layered porous structure, a spherical porous structure, a cylindrical porous structure or an amorphous porous structure;

[0086] The nanofiber aerogel has a thickness of 0.1 to 100 mm, a fiber diameter of 10 to 1000 nm, and a volume density of 1 to 20 mg / cm 3 , porosity is 50-99.99%; the average sound absorption coefficient of the nanofiber aerogel is 0.4-0.7, and the oil absorption is 30-80g / g; the effective peak width of electromagnetic wave absorption of the nanofiber aerogel is >5GHz, and the minimum reflection loss is <-20dB; it shows good microwave absorption performance.

[0087] The material prepared by the present invention is an ultra-light material with an interconnected pore structure and a wide adjustable range of the pore structure, which is beneficial to improving multifunctional application performance.

[0088] The above description is only a preferred embodiment of the present invention and is not any formal or substantial limitation of the present invention. It should be pointed out that a person skilled in the art can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention.

Claims

1. A freeze-drying-free, low-cost and rapid method for preparing large-sized elastic nanofiber aerogels, characterized in that: The following steps are involved: The first step: dispersing the nanofibers and polysaccharide polymers in water to form a dispersion; Step 2: solidifying the dispersion to form a solidified mass; Step 3: placing the solidified block into an ethanol solution of a metal cation salt to undergo coordination reaction to form a wet gel; Step 4: Remove the solvent from the wet gel under normal pressure to obtain nanofiber aerogel.

2. The method according to claim 1, characterized in that The raw material of the nanofiber in the first step is selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polysulfone, polystyrene, polyimide, polymethyl methacrylate, polyetherimide, polyurethane, polyamide, polyaniline, bacterial cellulose, cellulose acetate, silicon dioxide, titanium dioxide, aluminum oxide, carbon nanotubes and graphene; The polysaccharide polymer is selected from at least one of chitosan, sodium alginate, hyaluronic acid, chitin, sodium carboxymethyl cellulose, starch, keratan sulfate and chitin.

3. The method according to claim 1, characterized in that The solidification treatment in the second step includes: freezing and forming in a mold; And / or, the metal cation salt in the third step is at least one of cupric chloride, lanthanum chloride, cerous chloride, ferric chloride, cobalt chloride, nickel chloride, cupric chloride, zinc chloride, calcium chloride, zinc nitrate, ferric nitrate and cupric nitrate.

4. The method according to claim 1, characterized in that Conductive components and magnetic nanoparticles are also added to the dispersion in the first step.

5. The nanofiber aerogel prepared by the method according to any one of claims 1 to 4.

6. The nanofiber aerogel according to claim 5, characterized in that The shape of the nanofiber aerogel is a cylinder, a pyramid, a cube, a regular hexahedron or a regular octahedron; And / or, the microstructure of the nanofiber aerogel is a layered porous structure, a spherical porous structure, a cylindrical porous structure or an amorphous porous structure.

7. The nanofiber aerogel according to claim 5, characterized in that The thickness of the nanofiber aerogel is 0.1 to 100 mm, and the volume density is 1 to 20 mg / cm 3 .

8. The nanofiber aerogel according to claim 5, characterized in that The average sound absorption coefficient of the nanofiber aerogel is 0.4 to 0.7; And / or, the oil absorption of the nanofiber aerogel is 30 to 80 g / g.

9. The nanofiber aerogel according to claim 5, characterized in that: The nanofiber aerogel has an effective peak width of electromagnetic wave absorption of >5 GHz and a minimum reflection loss of <-20 dB.

10. Application of the nanofiber aerogel prepared by the method according to any one of claims 1 to 4 in wave absorbing materials, sound absorption and noise reduction, heat insulation, filtration separation and tissue engineering.

Citation Information

Patent Citations

  • A supercritical drying method for preparing ultra-low density aerogels and the product obtained by the method.

    CN110553470B

Cited By

  • Cationic etherifying agent modified starch composition and preparation method thereof

    CN120625405A

  • A cationic etherifying agent modified starch composition and its preparation method

    CN120625405B